Processo de ensino e aprendizagem de álgebra linear no ensino superior permeado pelo uso de tecnologias digitais: uma revisão sistemática de pesquisas brasileiras - (:unkn) unknown (Universidade Federal do Pampa, 2020)
This research aimed to investigate the potentialities, and/or obstacles, of the use of digital technologies in the process of teaching and learning Linear Algebra in Higher Education. As a theoretical framework, the theory of semiotic representation records is adopted. This is a qualitative research defined as a systematic review according to Kitchenham. The research was conducted nationwide in Brazilian journals available online, which had Qualis Capes above the Stratum of B2 in the area of Education of the last 10 years. As results, it is pointed out, in particular, that the use of digital technologies has potentials as communication in natural language among the agents involved in the teaching and learning process, the records of semiotic representations are part of this communication, as well as, the understanding of mathematical concepts begins through the record of representation in natural language relating to the other records of representation of mathematics, the lack of use of mathematical resources has been identified, in addition to the need for digital technological resources that enable simultaneous work between teachers and academics, exploration and mobilization of the different records of semiotic representation by students.
Keywords: Álgebra linear; Tecnologias digitais; Registros de representação semiótica; Revisão sistemática; Linear algebra; Digital technologies; Records of semiotic representation; Systematic review; CNPQ::CIENCIAS EXATAS E DA TERRA